- #1

nomadreid

Gold Member

- 1,434

- 141

## Main Question or Discussion Point

((-8)^2)^(1/3)=64^(1/3)=4

(-8)^(1/3))^2 = (-2)^2=4

but

(-8)^(2/3) = 4(-1)^(2/3) = 4((2/3)(cos (π) + i*sin(π)) and so forth, giving a complex number.

I understand why the latter one works. Why don't the first two?

Thanks.

(-8)^(1/3))^2 = (-2)^2=4

but

(-8)^(2/3) = 4(-1)^(2/3) = 4((2/3)(cos (π) + i*sin(π)) and so forth, giving a complex number.

I understand why the latter one works. Why don't the first two?

Thanks.